Mitigating Financial Burden of Elderly through Social Protection Schemes: Issues and Challenges for Pakistan - Raza, Hasan; Ahmed, Farooq; Mohiuddin, Zaeema Asrar; Osama, Ahmed (International Journal of Emerging Trends in Social Sciences, 2017)
The study on social protection programs for elderly in Pakistan indicates an absence of concrete and clear frameworks developed by government. Most social security and cash assistance programs for the elderly are ad hoc arrangements which are made in response to circumstantial demands or advocated by international donor organizations which usually have their own agenda and priority. Ageing is the reality of every individual’s life therefore it is important to save the social status of elderly people & ensure a progressive life. It is also observed that there are programs and frameworks but contains duplication and overlapping that create hurdles in designing a comprehensive and purposeful social protection strategy for elderly in Pakistan. The lack of such initiatives can cause difficulty for elderly people in planning their future. This paper presents a review of available programs offered for elderly in Pakistan in order to reduce the financial burden and what challenges are faced by them in accessing information about these programs. The paper also looks at identifying gaps and suggests a “way forward” for future contribution towards this important yet ignored issue. The paper recommends that social protection have been categorized in policies process, design and delivery & financing and they must be planned, monitored& evaluated effectively to improve the quality of life of elderly people in Pakistan.